Removal of humic substances in water by granular activated carbon - Ilavský, Ján; Barloková, Danka; Kapusta, Ondrej (International Conference “Environmental Engineering”, 2017)
The basic characteristics of humic substances and their negative influence on water quality and its treatment are described. The paper presents the results of removing humic substances from water from the Hriňová (Slovakia) water reservoir with the addition of humic substances using granular activated carbon (GAC) from two producers (Chemviron, Cabot) at three different pH levels of water. The results of static experiments involving the removal efficiency of humic substances using TOC parameters and the instantaneous water adsorption capacity, which uses materials at the contact time of the water with GAC material, was calculated. The results show that the pH of the water had no significant effect on the change in the efficiency of removing humic substances from water. A high level of efficiency (50%) and the lowest value of TOC are obtained at a pH of 6.5. The GAC adsorption capacity of humic substances, depending on the contact time with the water, ranged from 0.17 mg/g for one hour to 0.56 mg/g for eight hours of contact time. The most effective material was Filtrasorb F400.